(untitled) (Fiep Bulletin - online, 2014)
The levels of insatisfaction with the body image, are surely related to the beauty patterns exposed by the media, the search for the “worked out” body becomes to compulsion, in the search for the ideal anatomy (LABRE, 2002). The worry about the stetic and the satisfaction with the body image are factors that get through the human beings history, through the times, giving value to such a determined perfect body stereotype, which are wanted by some subjects from social, intellectual and gender classes different. This search aims to propose the thoughts of teachers and searchers about real esthetics patterns and levels of insatisfaction with the body image, just like discussing the responsibility of Physical Education at school, trying to get efficient interventive processes, through the literary review analysis.